Detection of Small Numbers of Campylobacter jejuni and Campylobacter coli Cells in Environmental Water, Sewage, and Food Samples by a Seminested PCR Assay - Waage, Astrid S. (American Society for Microbiology, 1999)
A rapid and sensitive assay was developed for detection of small numbers of Campylobacter jejuni and Campylobacter coli cells in environmental water, sewage, and food samples. Water and sewage samples were filtered, and the filters were enriched overnight in a nonselective medium. The enrichment cultures were prepared for PCR by a rapid and simple procedure consisting of centrifugation, proteinase K treatment, and boiling. A seminested PCR based on specific amplification of the intergenic sequence between the two Campylobacter flagellin genes, flaA and flaB, was performed, and the PCR products were visualized by agarose gel electrophoresis. The assay allowed us to detect 3 to 15 CFU of C. jejuni per 100 ml in water samples containing a background flora consisting of up to 8,700 heterotrophic organisms per ml and 10,000 CFU of coliform bacteria per 100 ml. Dilution of the enriched cultures 1:10 with sterile broth prior to the PCR was sometimes necessary to obtain positive results. The assay was also conducted with food samples analyzed with or without overnight enrichment. As few as ≤3 CFU per g of food could be detected with samples subjected to overnight enrichment, while variable results were obtained for samples analyzed without prior enrichment. This rapid and sensitive nested PCR assay provides a useful tool for specific detection of C. jejuni or C. coli in drinking water, as well as environmental water, sewage, and food samples containing high levels of background organisms.